Solar Tracking and Automatic Sprinkler Irrigation - Felicia Tang Bing Ying; Ahmad Alabqari Ma'Radzi; Tengku Nadzlin Tengku Ibrahim (Multidisciplinary Applied Research and Innovation, 2024)
Solar energy is an increasingly popular renewable energy source, however, maximising its efficiency and utilisation is crucial for long- term energy production. This project focuses on designing and implementing a Solar Tracking and Automatic Sprinkler Irrigation system to improve solar panel efficiency and automate plant watering. The objective is to develop a system that can track the sun’s movement and adjust the position of the solar panels accordingly to maximise efficiency. Additionally, the system will automatically water plants based on specified parameters in order to improve plant growth. The system utilises a microcontroller, sensors, motors, and a water pump to achieve these duties. The project’s results show improved solar panel efficiency and increased plant growth due to the automated irrigation system. Overall, the Solar Tracking and Automatic Sprinkler Irrigation system presents an innovative solution to enhance renewable energy production and agricultural practices.